Doors, Closets, Attics and Basements. Architecture and the Distribution of the Sensible - Rispoli , Ramon (E|C, 2023)
This article delves into the concept of dirt, its management, and its relationship with architectural spaces. Drawing from anthropologist Mary Douglas’s perspective, dirt is viewed as something inherently “out of place”, intrinsically connected to the idea of order and its disruption. Accordingly, cleaning is considered a domestic ritual of purification, serving the purpose of constantly reestablishing an order that remains under threat. The study also explores how architecture operates as a “technology of partitioning”, delineating the boundaries between what is visible and invisible, exposed and concealed. It investigates the significance of architectural elements, such as doors, in shaping the politics of spaces and their organization. Furthermore, the article examines the association between the notion of dirt and time, shedding light on the role of maintenance practices that often remain inconspicuous, both within the realm of architecture and art.